RELATIONSHIP BETWEEN MENTAL TOUGHNESS AND TRAIT ANXIETY IN SPORTS - ANALUIE HOSSEIN,; REZA FARUQUE MOHD,; SAHA SOUMENDRA,; HASHIM HAIRUL ANWAR,; MUSTAPHA MUZAIMI, (International Journal of Pharma and Bio Sciences, 2016)
The attribute of mental toughness terminologically could be explained as an interactive combination of stable humane characteristics which inspires him or her to strive persistently for excellence. Though the concept of mental toughness is used widely, but comprehensive understanding of the construct based on empirical evidence is scanty. This research investigated the corroborative relationship between mental toughness and trait anxiety to determine whether mentally tough athletes generally experience more or less anxiety. We recruited 57 men (M age = 25.4 years, SD = 4.66) and 45 women (M age = 23.5 years, SD = 5.73), who are regular participants in a variety of sports. All of them were subjected to assessment of mental toughness using MTQ48, level of trait anxiety (which was assessed using the trait scale of State-Trait Anxiety Inventory (STAI-T)). Series of Pearson correlations between trait anxiety, overall mental toughness, and the six subscales of mental toughness showed significant (p>0.05) correlations. No significant differences were evident in overall mental toughness and mental toughness dimensions between men and women, whereas trait anxiety was observed as significantly different between male and female players. Our findings however suggest the relevance and importance of trait anxiety in the assessment and development of mental toughness among athletes.